The mediating role of E‐learning motivation on the relationship between technology access and satisfaction with E‐learning - Adnan Innab; Naji Alqahtani (Nursing Open, 2023)
Abstract Aim To examine the e‐learning motivation mediating role on the relationship between technology access and satisfaction with e‐learning among nursing students during COVID‐19 pandemic. Design This is a cross‐sectional, descriptive design. Methods A convenience sample of students (N = 139) from public and private nursing colleges was recruited in this study. Data were collected using students' satisfaction, motivation and access to technology tools. Results Nursing students in the study were somewhat satisfied with e‐learning, had access to the required technology for e‐learning and had moderate levels of e‐learning motivation. The multiple regression analysis showed that technology access and e‐learning motivation influenced and explained 30.4% of the variance in satisfaction with e‐learning. Previous experience with e‐learning was associated with satisfaction with e‐learning. A series of regression analyses revealed that e‐learning motivation partially mediated the relationship between technology access and satisfaction with e‐learning.